Phylogenomics of Xanthomonas field strains infecting pepper and tomato reveals diversity in effector repertoires and identifies determinants of host specificity - Schwartz, Allison R.; Potnis, Neha; Timilsina, Sujan; Wilson, Mark; Patané, José; Martins, Joaquim; Minsavage, Gerald V.; Dahlbeck, Douglas; Akhunova, Alina; Almeida, Nalvo; Vallad, Gary E.; Barak, Jeri D.; et al. (Frontiers in Microbiology, 2015)
Bacterial spot disease of pepper and tomato is caused by four distinct Xanthomonas species and is a severely limiting factor on fruit yield in these crops. The genetic diversity and the type III effector repertoires of a large sampling of field strains for this disease have yet to be explored on a genomic scale, limiting our understanding of pathogen evolution in an agricultural setting. Genomes of sixty-seven Xanthomonas euvesicatoria (Xe), Xanthomonas perforans (Xp), and Xanthomonas gardneri (Xg) strains isolated from diseased pepper and tomato fields in the southeastern and midwestern United States were sequenced in order to determine the genetic diversity in field strains. Type III effector repertoires were computationally predicted for each strain, and multiple methods of constructing phylogenies were employed to understand better the genetic relationship of strains in the collection. A division in the Xp population was detected based on core genome phylogeny, supporting a model whereby the host-range expansion of Xp field strains on pepper is due, in part, to a loss of the effector AvrBsT. Xp-host compatibility was further studied with the observation that a double deletion mutant of AvrBsT and XopQ in Xp experiences a host gain for Nicotiana benthamiana. Extensive sampling of field strains and an improved understanding of effector content will aid in efforts to design disease resistance strategies targeted against highly conserved core effectors.